Presentase Kayu Teras dan Kayu Gubal serta Penentuan Kayu Juvenil dan Kayu Dewasa pada Lima Kelas Umur Jati (Tectona grandis L.f.) The Percentage of Heartwood and Sapwood and Determination of Juvenile and Mature Wood on Five Age-Class of Teak (Tectona grandis L.f.) - Atmawi Darwis; Rudi Hartono; Sansan Sarif Hidayat (Jurnal Ilmu dan Teknologi Kayu Tropis, 2005)
Teak wood is one of fancy woods with durability class I ~ II and strength class II and has very beautiful decorative value. The existence of heartwood has more value than sapwood, because of the color and its high natural durability. The high proportion of Teak heartwood will increase higher benefit and sale value (economic value). The existence of juvenile wood is generally less liked then mature wood because of its characteristics. However, determining juvenile wood is not as easy as determining heartwood from sapwood. One of the methods is to see the variation of fiber length from pith to bark.The purposes of this research were to find out the percentage of heartwood and sapwood and also to know the time when juvenile wood becoming mature wood on five age-class of Teak (I ~ V).The research results showed that during the increasing of teak age-class, the percentage of heartwood was also growing and on the contrary, the percentage of sapwood was decreasing. During the process of determining juvenile wood from mature wood, the result proved that on teak wood with the age-class I ~ II, the fiber length showed increment so that the process of forming into mature wood was not yet to be seen. While teak with the age-class III ~ V showed that the form of mature wood started to show up after the 11th or 12th annual increment